(untitled) (Khairulummah, 2023)
Ilm ul Allal is undoubtedly the hardest and complex discipline in the studies of Hadith. Kitab ut Tameyyez is the easiest book on this topic in which Imam Muslim has elaborated upon many a complex issues in an easy to follow, logical way. Like any other book on Hadith, Kitab it Tameyyeez distinguishes Hadith into three groups: One, in which the context of Hadith is contentious, two, those Hadith which have dubious chain of narration, and third those sayings/ Hadith in which both context and chain of narration are debatable. In this article, not only a critique of Imam Muslim’s methodology shall be given but a brief critical overview of those Hadith shall also be attempted which have weak authentication in terms of consistency and continuity of chain of narration. They are three in number.